Oppression versus liberation: Representation of hijab in two post-9/11 British literary texts - Hasan, Md. Mahmudul (Brill, Leiden, Netherlands, 2016)
This article analyzes the representation of hijab and of hijab-wearing women in two post-9/11 British literary texts, Leila Aboulela’s Minaret (2005) and Shelina Janmohamed’s Love in a Headscarf (2009). It discusses the strong resolve of the heroines of these works with regard to wearing the hijab despite opposition to it from within their peers, friends and family members as well as Islamophobic hostility to this most overt and visible marker of Muslim identity. While many women wear hijab instinctively and without question in order to follow their religion and cultural tradition, Najwa in the fictional work Minaret and Shelina in the memoir Love in a Headscarf decide to wear it reflectively after long contemplation and much soul searching. Such experiences convincingly and creatively refute the assumption that hijab is imposed on Muslim women by male relatives and dispel the most widespread stereotype that it is synonymous with female oppression.